Transforming bridges into smart infrastructure: a data-driven approach to monitoring bats and promoting sustainable coexistence - Koch, Jacob; Kropczynski, Jess; Perez-Jimenez, Janette; Johnson, Joseph S. (Information Research an international electronic journal, 2025)
Introduction. Smart infrastructure development often prioritizes human needs such as safety and efficiency, overlooking the potential to facilitate coexistence with wildlife. This paper addresses this gap by demonstrating innovative use of internet of things (IoT) technology and data visualization for ecological monitoring. Method. We repurposed commercially available wildlife trail cameras to collect data on bats roosting in bridges, despite commercial devices not being built for this application. Furthermore, we developed a map- and cloud-based dashboard to integrate this ecological data with existing bridge metadata, transforming raw sensor data into actionable insights for transportation authorities. Analysis. We explore the ability of the dashboard to meet decision-making needs and offer design implications to further advance wildlife-inclusive smart infrastructure efforts. Results. Our findings demonstrate the efficacy of using IoT devices for wildlife monitoring and the power of data visualization in informing conservation efforts within smart infrastructure development. Conclusions. This study showcases the potential of IoT-enabled cameras and a user-friendly dashboard, BatMap, for effective bat monitoring and informed decision-making in infrastructure projects.